Retrofitting Typestates into Rust - Duarte, José Miguel Gonçalves (2021)
As software becomes more prevalent in our lives, bugs are able to cause significant disruption. Thus, preventing them becomes a priority when trying to develop dependable systems. While reducing their occurrence possibility to zero is infeasible, existing approaches are able to eliminate certain subsets of bugs. Rust is a systems programming language that addresses memory-related bugs by design, eliminating bugs like use-after-free. To achieve this, Rust leverages the type system along with information about object lifetimes, allowing the compiler to keep track of objects throughout the program and checking for memory misusage. While preventing memory-related bugs goes a long way in software security, other categories of bugs remain in Rust. One of which would be Application Programming Interface (API) misusage, where the developer does not respect constraints put in place by an API, thus resulting in the program crashing. Typestates elevate state to the type level, allowing for the enforcement of API constraints at compile-time, relieving the developer from the burden that is keeping track of the possible computation states at runtime, and preventing possible API misusage during development. While Rust does not support typestates by design, the type system is powerful enough to express and validate typestates. I propose a new macro-based approach to deal with typestates in Rust; this approach provides an embedded Domain-Specific Language (DSL) which allows developers to express typestates using only existing Rust syntax. Furthermore, Rust’s macro system is leveraged to extract a state machine out of the typestate specification and then perform compile-time checks over the specification. Afterwards we leverage Rust’s type system to check protocol-compliance. The DSL avoids workflow-bloat by requiring nothing but a Rust compiler and the library itself.